Medical Gas Therapy for Tissue, Organ, and CNS Protection: A Systematic Review of Effects, Mechanisms, and Challenges. Issue 13 (4th March 2022) - Zafonte, Ross D.; Wang, Lei; Arbelaez, Christian A.; Dennison, Rachel; Teng, Yang D.
Abstract: Gaseous molecules have been increasingly explored for therapeutic development. Here, following an analytical background introduction, a systematic review of medical gas research is presented, focusing on tissue protections, mechanisms, data tangibility, and translational challenges. The pharmacological efficacies of carbon monoxide (CO) and xenon (Xe) are further examined with emphasis on intracellular messengers associated with cytoprotection and functional improvement for the CNS, heart, retina, liver, kidneys, lungs, etc. Overall, the outcome supports the hypothesis that readily deliverable "biological gas" (CO, H2, H2 S, NO, O2, O3, and N2 O) or "noble gas" (He, Ar, and Xe) treatment may preserve cells against common pathologies by regulating oxidative, inflammatory, apoptotic, survival, and/or repair processes. Specifically, CO, in safe dosages, elicits neurorestoration via igniting sGC/cGMP/MAPK signaling and crosstalk between HO‐CO, HIF‐1 α /VEGF, and NOS pathways. Xe rescues neurons through NMDA antagonism and PI3K/Akt/HIF‐1 α /ERK activation. Primary findings also reveal that the need to utilize cutting‐edge molecular and genetic tactics to validate mechanistic targets and optimize outcome consistency remains urgent; the number of neurotherapeutic investigations is limited, without published results from large in vivo models. Lastly, the broad‐spectrum, concurrent multimodal homeostatic actions of medical gases may represent a novel pharmaceutical approach to treating critical organ failure and neurotrauma. Abstract : This systematic review is focused on tissue protections, mechanisms, data qualities, and translational challenges of experimental gas therapies. The outcome suggests that biological/noble gases in safe dosages preserve cells by modulating oxidative, inflammatory, apoptotic, survival, and/or repair processes; it remains urgent to validate therapeutic targets via cutting‐edge molecular/genetic technologies. Gas agents may be developed to treat organ failure and neurotrauma.